Dynamic modeling of the secondary drying stage of freeze drying reveals distinct desorption kinetics for bound water. Issue 3 (17th February 2016) - Trelea, Ioan Cristian; Fonseca, Fernanda; Passot, Stéphanie
ABSTRACT: In freeze drying, the desorption step for reaching a low target moisture content may take a significant fraction of the total process duration. Because the long-term stability of freeze-dried biological products strongly depends on the current moisture content, modeling the desorption process may help safely optimize the secondary drying step. Most published models assume a first-order desorption kinetic, but experimental evidence shows that strongly bound water in the monolayer takes a much longer time to be desorbed than less bound water in multilayer. The proposed model for desorption of freeze-dried lactic acid bacteria preparation accounts for monolayer and multilayer water state in the solid matrix, with very different desorption kinetics. Results showed that the ratio of characteristic desorption times (monolayer/multilayer) was almost 30. Temperature dependence was adequately described by an Arrhenius law in the range of 15 to 40°C. Model parameter identification used simultaneously gravimetric measurements with high time resolution and direct Karl-Fisher titration, from several experiments at different, time-varying temperatures.